Cave millipeds of the United States. XI. Opiona graeningi, n. sp., a troglomorphic caseyid milliped from Siskiyou County, California, with comments on the genus Opiona Chamberlin 1951 (Diplopoda, Chordeumatida, Caseyidae) - Shear, William A. (Zootaxa, 2011)
The new species Opiona graeningi is described from caves in the Marble Mountain Wilderness Area, Klamath National Forest, Siskiyou Co., California, as the first troglomorphic species of Opiona, the first troglobiont from the globally important Klamath Siskiyou ecoregion, and possibly the first troglobiotic caseyid. Notes are provided on the composition of the genus Opiona and on the interpretation of the gonopods. Opiona, with 13 described species, may not be monophyletic.